CURRICULUM ADEQUATION IN COMMON ROOM FOR STUDENT WITH TEA: WORKING THE THEME OF ELECTION - Machado, Priscila Rocha [UNESP]; Messias Filaho capellini, Vera Lusia [UNESP] (Univ Federal Mato Grosso Sul, 2016)
Countless are the experiences of each teacher in the course of his career. Having the opportunity to teach for a student with disabilities and this being directed to the Global Development Disorders (PDD), the teacher's learning to further extend. Making use of a practice developed by the teacher, also one of the authors of this channeled to the educational and social development of a student with autism spectrum disorder (ASD) of the fifth year of elementary school in a public school in the state Sao Paulo aimed to describe the curricular adaptations of disciplinary content main theme of history held by ordinary classroom teacher so that students could develop their functionality. Based on a case study reported in gradebook, this research is presented as a reflection on the ordinary classroom teacher work on the necessary adjustments in their program content so as to meet the student with Disorder ASD and expose doubts, successes and failures in this activity necessary curricular adjustments in everyday school life. From the theme 'Municipal Elections 2016', the teacher sought, through association activities of words and images, work in pairs, dramatizations of historical fact, individualized care in the portfolio with the student, methods so that they could understand and participate the work proposed in a context that would give meaning to what was being outlined. The results were positive since seized the attention and participation of students in activities worked, corresponding to the pre-established expectations by the teacher to the student's development. It was possible autonomy in solving proposed and greater familiarization problems with words and terms associated with municipal elections. These results ultimately incite new adjustments that provide not only the teaching and learning of students with ASD, but their autonomy and self-confidence in their capabilities.
Keywords: Special Education; School inclusion; Disorder Autistic Spectrum (TEA); Curricular Adaptations